Evaluation of the effect of essential oils of Cinnamomum zeylanicum and Eucalyptus globulus against Salmonella Enteritidis and Salmonella Gallinarum in broilers (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This study intended to assess the effect of Cinnamomum zeylanicum and Eucalyptus globulus essential oils (Eos) as an alternative to antibiotics on Salmonella spp. infection, antibiotic growth promotion, and immunomodulation in experimentally infected broiler chickens. Materials and Methods: Broiler chicks (n = 135) were randomly and equally divided into nine groups. From day 1, experimental groups were dietary supplemented with C. zeylanicum or E. globulus EOs. Salmonella Enteritidis (SE) and Salmonella Gallinarum (SG) counts in droppings, growth performance (weight gain, feed conversion ratio), humoral immune response to Newcastle Disease Virus (NDV) and Infectious Bursal Disease Virus (IBDV), and gut morphology were measured in birds. Results: The antibiotic groups and the positive control group recorded significantly higher SE and SG counts compared to the EO groups. Cinnamomum zeylanicum recorded the highest reduction in SE and SG counts. Birds fed EOs gained weight much faster on day 35 and improved their NDV and IBDV titers. Supplementation with the EO resulted in the lengthening of villi and an increase in mucosal surface area in various intestinal sections, including the duodenum, jejunum, and ileum, as observed under the microscope, indicating an improvement in gut function. Conclusion: Cinnamomum zeylanicum and E. globulus EOs both exhibited a high in vivo anti-Salmonella effect, better growth performance, and improved immune and gut conditions in broilers. These results support the use of plant-based EOs as natural and antibiotic-free alternatives for controlling Salmonella infections in chicken.J. Adv. Vet. Anim. Res., 12(4): 1097–1107, December 2025http://doi.org/10.5455/javar.2025.l970